In Vitro Antioxidant, Antimicrobial, Anticoccidial, and Anti-Inflammatory Study of Essential Oils of Oregano, Thyme, and Sage from Epirus, Greece - Erasmia Sidiropoulou; Virginia Marugán-Hernández; Ioannis Skoufos; Ilias Giannenas; Eleftherios Bonos; Kensilandia Aguiar-Martins; Diamanto Lazari; Theodora Papagrigoriou; Konstantina Fotou; Katerina Grigoriadou; Damer P. Blake; Athina Tzora (Life, 2022)
Origanum vulgare subsp. hirtum, Thymus vulgaris, and Salvia fructicosa are aromatic plants commonly found in Mediterranean countries and are traditionally used in Greece as a remedy for humans, since they are well known as potent antibacterial, antioxidant, and anti-inflammatory agents. Essential oils (EOs) derived from plants cultivated in the mountainous region of Epirus, Greece, were investigated for their inhibitory activity against key microorganisms with relevance to avian health, while also assessing their antioxidant and anti-inflammatory activity. The total phenolic content (TPC) of the EOs was estimated according to the Folin–Ciocalteu method, while the antioxidant capacity was tested through the EOs’ ability to scavenge free radicals by means of the DPPH, ABTS, and FRAP assays. Antibacterial and anti-inflammatory effects were examined by the agar disc diffusion method and the lipoxygenase (LOX) inhibition test, respectively. Furthermore, the EOs’ ability to inhibit the invasion of sporozoites of Eimeria tenella (Wisconsin strain) along with any toxic effects were assayed in Madin–Darby bovine kidney (MDBK) cells. The antioxidant activity of the EOs was observed in descending order: oregano > thyme > sage. The antimicrobial effects of thyme and oregano were equivalent and higher than that of sage, while the anti-inflammatory effect of thyme was higher compared to both sage and oregano. The intracellular invasion of sporozoites was evaluated by the detection of E. tenella DNA by qPCR from cell monolayers harvested at 2 and 24 h post-infection. Parasite invasion was inhibited by the addition of oregano essential oil at the concentration of 100 μg/mL by 83% or 93% after 2 or 24 h, respectively, and was higher compared to the addition of thyme and sage, which had similar effects, but at a less intensive level. The cytotoxic assessment of all three essential oils revealed that they had no effect on MDBK cells compared to dimethyl sulfoxide (DMSO), used as the control substance. The supplementation of oregano, thyme, and sage essential oils had a potent antioxidant, anti-inflammatory, antimicrobial, and anticoccidial in vitro effect that is comparable to synthetic substances or approved drugs, justifying the need for further evaluation by in vivo studies in broilers reared in the absence of antimicrobial and anticoccidial drugs or synthetic antioxidant and/or anti-inflammatory compounds.